Исследование процесса разрушения прочных горных пород при бурении дегазационных скважин на шахтах Донбасса долотами, оснащенными алмазно–твердосплавными пластинами - Свешников, И.А.; Скляров, Э.Д.; Заболотный, С.Д.; Беспалов, С.Ф. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
In a paper the studies on a justification of a rational construction of bits equipped with diamond-hardmetal plates (DHP) are resulted. On a foundation of study of a pitch of cutting Т the rational schema of DHP arranging in fans of a bit supplying minimum energy output of breaking down of a massif of strong abrasive sandstones is instituted. On a foundation of the held studies the bit for boring methane drainage boreholes on mines of Donbass is designed, manufactured and tested.